1979
DOI: 10.1002/1097-0142(197912)44:6<2254::aid-cncr2820440638>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Nerve entrapments associated with postmastectomy lymphedema

Abstract: Ninety females underwent mastectomy for breast cancer and were thereafter investigated to determine whether nerve entrapments were responsible for some of the disabling symptoms in their arms. The majority of these patients suffered from fullness (edema), numbness, paraesthesia, weakness and pain of the arm on the mastecotmized side. Lymphedema of varying degrees found in 50% of these patients was associated with brachial plexus entrapment and carpal tunnel syndrome (CTS). 28% of the patients has CTS, and 28% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 15 publications
(2 reference statements)
3
31
0
1
Order By: Relevance
“…Lymphedema when occurs is commonly associated with chronic pain, arm deformity, and cellulites which may significantly lower patients’ function and quality of life. Moreover, it has been shown in one study that nearly 20% of patients developed carpel tunnel syndrome following ALND (10). Thus, it is not rare to encounter such patients with different hand conditions that require elective surgery, but yet, despite the clear indication for surgery, most of these patients are never operated.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphedema when occurs is commonly associated with chronic pain, arm deformity, and cellulites which may significantly lower patients’ function and quality of life. Moreover, it has been shown in one study that nearly 20% of patients developed carpel tunnel syndrome following ALND (10). Thus, it is not rare to encounter such patients with different hand conditions that require elective surgery, but yet, despite the clear indication for surgery, most of these patients are never operated.…”
Section: Discussionmentioning
confidence: 99%
“…97,98 In this case, the patient developed symptoms consistent with moderately severe carpal tunnel syndrome 12 years after the onset of lymphedema. This patient has been seen for two separate episodes since her initial visit, the first in association with carpal tunnel release surgery and the second following an infection of unknown origin in the olecranon bursa.…”
Section: Factors That Require New Episodes Of Carementioning
confidence: 76%
“…19 Almost all of these patients had local metastases, but only 9 had been previously irradiated. We have not found that arm edema alone, however severe, causes the BPS; the 28 patients we have followed for years with severe arm edema unrelated to locoregional recurrence retained the ability to abduct their arms to 180° (Braverman AS, unpublished data).…”
Section: Discussionmentioning
confidence: 99%